Hands-On GUI Application Development in Go Build Responsive, Cross-Platform, Graphical Applications with the Go Programming Language. - Williams, Andrew (Packt Publishing Ltd, 2019)
Hands-On GUI Application Development in Go will help you to extend your knowledge of Golang and become a confident graphical application developer with Go. The book explores many graphical libraries available for Go to show how GUIs can be created for applications. This book is a guide to the most popular Go GUI Frameworks and techniques.